Filsafat Ilmu sebagai Fondasi Pengembangan Penelitian Pendidikan: Kajian Literatur: Penelitian - Hendriyadi; Rahmi Susanti; Yosef; Umi Chotimah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to examine the role of philosophy of science as a foundation in the development of educational research through a literature review approach. Departing from the need to strengthen the epistemological, ontological, and axiological foundations in educational research, this study highlights the problem of weak conceptual frameworks in many studies that impact the quality of scientific findings. The analysis was conducted by examining various relevant literature, including Popper's theory of falsificationism, Kuhn's views on scientific paradigms, and Habermas's ideas on the importance of knowledge. The method used was a systematic literature review with source searches through indexed national and international journals. The results of the study indicate a gap between educational research practices and epistemological standards of philosophy of science, particularly regarding paradigm clarity, methodological validity, and theoretical justification. This study offers a model for strengthening educational research based on philosophy of science that places critical, reflective, and transformative rationality as its main pillars. These findings emphasize that the integration of philosophy of science not only improves research quality but also expands academic contributions and educational practice. Thus, this study makes a theoretical contribution to the development of the state of the art in methodological studies while offering a novel integrated conceptual framework for educational research in the contemporary era.